Heavy Flavour Physics Theory and Experimental Results in Heavy Quark Physics - Davies, C; Playfer, S M; Osborne, P (Taylor & Francis, 2002)
This book provides a thorough introduction to the phenomenology of heavy flavour physics, those working on the B-factories, LHCb, BTeV, HERA and the Tevatron. It explains how heavy quark theory could be implemented on the lattice, and discusses the status of CP-violation in the neutral kaon system.